EFFECTIVENESS OF FINANCIAL ADMINISTRATION IN MANIPUR IN THE RECENT YEARS - Singh, Nobin Khumanthem; Singh, Khundrakpam Jayantakumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study primarily utilized secondary data as tools for analysis, including sources published by the Government of Manipur, such as the Annual Finance Statement, Economic Survey of Manipur, Report of the Comptroller and Auditor General of India, and the Handbook of Statistics on Indian States by the Reserve Bank of India and the Government of India. The findings emphasize that a sound and robust financial framework is crucial for effective governance. Therefore, the financial machinery of the state must be regulated systematically to ensure both current efficiency and future developmental prospects. Furthermore, governmental departments need to coordinate effectively and ensure financial assistance to prevent the underutilization of resources. This requires a focus on economic development through enhanced activities and strategic planning. The analysis reveals that Manipur’s tax elasticity is higher compared to the national average. As a result, the Central Government should prioritize tax devolution specifically for Manipur. Additionally, reforms in the state’s financial policy and fiscal discipline are essential to improve its overall economic framework.